Grammatical Cause According to Al-Qastallani (d. 923 AH) in His Book Lata’if al-Isharat li Funun al-Qira’at: A Model of Conjugated Verbs - Jabeer, Sameer; Ali , Lina (Al-Adab Journal, 2025)
The Grammatical Cause in Al-Qastallani’s (d. 923 AH) Work "Latā'if al-Ishārāt li-Funūn al-Qirā'āt": A Study of Conjugated Verbs as a ModelThis research addresses the grammatical cause in conjugated verbs as discussed by Al-Qastallani in his book Latā'if al-Ishārāt li-Funūn al-Qirā'āt. The topic of grammatical causation is considered one of the most important aspects of Arabic grammar, originating with the early grammarians when they first laid down the foundational rules. Grammatical reasoning is an essential phenomenon in the Arabic language that cannot be disregarded.This study demonstrates that Al-Qastallani was deeply passionate about grammatical causation, as he rarely passed over a topic without explaining the underlying linguistic causes. In most of his explanations, he followed the reasoning methods of earlier grammarians, adhering mainly to the Basran school of thought. This was evident from his grammatical arguments and opinions, where he appeared as both a transmitter and interpreter of grammatical rules, often supporting them with Qur'anic verses and poetic examples to validate the grammatical principles. He used specific terms to indicate causation, such as "because," "for this reason," "due to," and "the lam of causation."Al-Qastallani was particularly concerned with explaining the grammatical, phonetic, and morphological rules in his work to clarify various rulings and solidify the correctness of Qur'anic readings. This, in turn, helps the listener understand complex issues and resolve ambiguities.